Obat-Obatan Laboratorium: Peran Kimia Medisinal Dalam Kesehatan - Husen, Desinta Nurohman; Amin, Saeful (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
Medicinal chemistry is a branch of science that combines the principles of chemistry and pharmacology to identify, evaluate, and assess drugs that have the potential to become new therapeutic agents. This article discusses the current state of medicinal chemistry and its applications in contemporary health, such as advances in treatment technology, computerization in medicinal chemistry, and innovations in contemporary medicinal chemistry. The methodology used is a systematic literature review related to scientific publications from 2018 to 2024. The research findings show that advances in computer technology, high- throughput screening, and structure-based drug design have accelerated the process of developing new drugs. In addition, there are other types of identification, such as peptide-based medicine, nanomedicine, and the use of intelligence in medicine. The main factors in the development of modern medicine include antimicrobial resistance, the ability to treat long- term diseases, and its bioavailability. The conclusion shows that medicinal chemistry remains an important foundation in the development of new therapies, with suggestions for improving multidisciplinary approaches, investing in computational technology, and focusing on personalized medicine approaches for more effective and safe drug development.